Taming the waters: strategies to domesticate the wicked problems of water resource management. (1st June 2005) - Lach, Denise; Rayner, Steve; Ingram, Helen
Increasing demands on water resource organisations are explored in three large US river basins: the Columbia River, Southern California, and the Potomac River Basin/Chesapeake Bay in the Washington DC metropolitan area. Interviews with staff of water management organisations revealed a strong preference for strategies that consolidate resources and over-build systems in order to provide reliable, low-cost, and safe water services. As challenges to these strategies emerge and as problems shift from tame to wicked, organisations develop strategies that spread the risks through cooperation. When domesticating strategies fail, some organisations have moved to local and adaptive negotiation of solutions with affected parties. The three management approaches reflect a general trend away from infrastructure-intensive strategies to social interaction-intensive strategies. Instead of managing the uncertainty of physical structures and organised routines, water resource agencies are beginning to "manage" ambiguous relationships with partners who have conflicting demands and needs.